Comparative Studies of Phytochemicals Analysis and in vitro Antioxidant Properties of Various Solvent Extracts of Sphaeranthus indicus Collected from three Different Climatic Zones of Central India - N. Akh, Pooja; Sharma1, Veena; K. Pathak2, Anupam (Asian Journal of Chemistry, 2021)
In present study, the total phenolic, flavonoid, tannin contents and the antioxidant activity of various solvent extracts of Sphaeranthus indicus collected from three different regions of central India were assessed. Plants extracts were prepared using Soxhlation method, while the total phenols, flavonoids and tannins were measured by the spectrophotometric method. DPPH, metal chelating, nitric oxide, superoxide oxide scavenging activity and FRAP, reducing power, total antioxidant assays were also evaluated. The highest phenolic contents 268.22 GAE equivalent, flavonoids 441.33 QE equivalents and tannin content was 120.32 tannic acid equivalents (mg/g) obtained from ethanolic extracts of sample SIEE-1 compared to other two plants extract. Similarly, the highest flavonoid contents was observed in SIAE-1 aqueous extract and lowest in SIAE-2 and SIAE-3. Extract of SIEE-1 possessed maximum antioxidant potentiality and SIAE-2 shown the least antioxidant activity in all assays. It could be concluded that different agroclimatic conditions have effects on the total phenolics, flavonoids, tannin contents and antioxidant potentiality of S. indicus plant.